International Assignments for Career Building: A Model of Agency Relationships and Psychological Contracts - Yan, Aimin; Zhu, Guorong; Hall, Douglas T. (Academy of Management Review, 2002)
Aimin Yan, Guorong Zhu, Douglas T. Hall, International Assignments for Career Building: A Model of Agency Relationships and Psychological Contracts, The Academy of Management Review, Vol. 27, No. 3 (Jul., 2002), pp. 373-391